UHMWPE acetabular cup creep deformation during the run-in phase of THA's life cycle - Zeman, Jakub; Ranuša, Matúš; Vrbka, Martin; Gallo, Jiří; Křupka, Ivan; Hartl, Martin (Journal of the mechanical behavior of biomedical materials, 2018)
Ultra-high molecular polyethylene (UHMWPE) is one of the most used materials of the acetabular liners in total tip arthroplasty (THA). Polyethylene has good tribological properties and biocompatibility. However, the lifetime of polyethylene implants is limited by wear related complications. Polyethylene material released into the periprosthetic environment induces osteolysis that can be followed by implant loosening. Wear of cup is influenced mainly by orientation of the cup in pelvis, by initial geometry before the material degradation and by tribological parameters. Aim of this study is to focus on the run-in-phase of the liner which is predictive for future life cycles of liner. Creep deformations of liners for 30°, 45°, 60° inclination angles surgically recommended for the positioning in pelvis were analyzed by the optical scanning method. Load tests were performed for 50,000 cycles. Creep deformations and surface changes were analyzed at each 10,000 cycles. The results showed that liners with 60° inclination angle had higher creep deformations. Penetration of femoral head was 0.04-0.05 mm and occupied bearing area was around 77%. The smallest creep was measured for the 45° angle. However, deformation in the superior quadrant of acetabular rim, which is vulnerable for potential fracture of a liner, was identified in this case. Topography of the surface bearing was also observed during the run-in-phase. The surface was smoothened and showed multidirectional scratches caused by the influence of third body particles. This phase was followed by early delamination. Flakes sized approximately 5-20 µm were observed on the UHMWPE surface. This is similar to the'flake' shape wear debris extracted in vivo. Detailed analysis of run-in phase of loading of modern polyethylene implants can help to distinguish between their creep deformation and true degradation. The latter contributes strongly to the development of wear related complications associated with THAs limiting substantially their time in service.
Keywords: Optical scanning; povrchové vlastnosti; Acetabulum; acetabulum; Mechanical Phenomena; časové faktory; náhrada kyčelního kloubu; Polyethylenes; Time Factors; Creep deformation; Arthroplasty, Replacement, Hip; Scanning Electron Microscopy; Surface Properties; Run-in-phase; polyethyleny; Inclination angle; UHMWPE; mechanické jevy